Religiosity is associated with hippocampal but not amygdala volumes in patients with refractory epilepsy. Issue 4 (16th March 2004) - Wuerfel, J; Krishnamoorthy, E S; Brown, R J; Lemieux, L; Koepp, M; Tebartz van Elst, L; Trimble, M R
Abstract : Objective: To assess the relationship between the behavioural triad of hyper-religiosity, hypergraphia and hyposexuality in epilepsy, and volumes of the mesial temporal structures. Method: Magnetic resonance images were obtained from 33 patients with refractory epilepsy and mesial temporal structure volumes assessed. Amygdala and hippocampal volumes were then compared in high and low scorers on the religiosity, writing, and sexuality sub-scales of the Neurobehavioural Inventory. Results: Patients with high ratings on the religiosity scale had significantly smaller right hippocampi. Religiosity scores rated by both patient and carer showed a significant negative correlation with right hippocampal volumes in this group. There were no other differences in amygdala or hippocampal volumes between these groups, or between high and low scorers on the writing and sexuality sub-scales. Conclusions: These findings suggest that right hippocampal volumes are negatively correlated with religiosity in patients with refractory epilepsy.